From blueprint to database. (Economist, 2008)
The article examines three-dimensional digital modeling in architectural design. Computer-aided design software still is used to create the actual plans of a building, with the three-dimensional models used for display purposes. Building-information modeling (BIM) software enables the architect to represent a building as a complete three-dimensional model with an associated database. One prominent architect to use the software is Frank Gehry.